Prevalence and Molecular Characterization of Giardia duodenalis in Calves in Turkey - Gultekin, Mehmet; Ural, Kerem; Aysul, Nuram; Ayan, Adnam; Balikci, Canberk; Toplu, Songul; Akyildiz, Gurkan (Acta Scientiae Veterinariae, 2017)
Background: Giardia duodenalis (G. duodenalis) is an ubiquitous, flagellated intestinal protozoan with major public health significance worldwide. Limited data are available on the epidemiology of G. duodenalis in dairy cattle from Turkey. Determining the zoonotic potential of the Giardia infection requires molecular characterization. The aim of the present study was to investigate the prevalence and to molecularly characterize G. duodenalis in calves less than three months of age in Aydin, Aegean region of Turkey. Materials, Methods & Results: The study was conducted on different dairy farms in the south-western part of the Turkey, Aegean Region, Aydin. A total of 198 Holstein Friesian calves less than three months of age, of both sexes were enrolled into the study. Faecal samples from each calf were collected manually from the rectum using a disposable latex glove. The consistency of collected samples was recorded as diarrhoeic or non-diarrhoeic. Diagnosis of G. duodenalis infection was made microscopically by detection of cysts in the faecal samples. One hundred and sixteen (58.5%) of the 198 faecal samples were diarrheic. Giardia cysts were found in 27 (23.28%) of the diarrheic samples and in 8 (9.76%) of nondiarrheic samples (P < 0.05). The overall prevalence of giardiosis in calves was determined as 17.67%. The prevalence of Giardia genotypes was identified by DNA sequence analysis of the beta-giardin gene for every PCR positive sample. The beta-giardin nested PCR assay was revealed assemblage A and sub-genotype A3 was detected in all of 35 samples (100%). Discussion: The highest prevalence of Giardia infection in calves is reported at the age between 1 and 6 months, and the prevalence shows decreased rate from the age of 6 months. The present study was conducted in Aydin, a province of south-western Turkey in the Aegean Region, and the overall prevalence from a total of 198 dairy calves was 17.67%. The prevalence rate in calves with diarrhoea was higher and reached up to 23.28%, whereas it was 9.76% in non-diarrhoeic calves. A prevalence study with molecular characterization of G. duodenalis isolates in cattle has not yet been reported from Turkey. Molecular studies have shown that mostly assemblage E predominates in cattle, but recent studies denoted that assemblage A is increasingly being detected and might be more widespread than expected before. In the present study, Giardia positive samples identified with a beta-giardin nested PCR assay. The sub-genotype A3 was identified in all samples. The same sub-genotype was identified in human and dog samples from different countries. Furthermore, sub-genotype A3 was found in humans and dogs from Turkey. In this context, results of the present study suggested an important role of calves as potential reservoirs of human infections in Turkey. In conclusion, epidemiological data revealed that G. duodenalis infection is frequent in calves with diarrhoea in Aydin, Turkey. The presence of the potentially zoonotic sub-genotype A3 and high prevalence of Giardia infection in diarrheic calves indicated the importance of treatment and necessary preventative measures. Further studies in human and animal populations living in this region are warranted regarding the zoonotic epidemiology of Giardia duodenalis.